Usage of ICT For Science Education In Some Renowned Bangla Medium School of Dhaka City (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present research explored the application of Information and Communication Technology (ICT) in Science Education at some selected renowned Bangla Medium Schools of Dhaka City Corporation Area, The study revealed that the main obstacles of practicing ICT in Science Education in these schools are insufficient number of science teachers and computers. Besides, lack of skilled lab teachers or trainers is also a constraint for practicing ICT. Albeit, there are multimedia facilities in most of the selected schools but currently only the RAJUK Uttara Model College of Dhaka Metropolitan Area uses this system properly. However, in recent times, only the students of eight renowned schools of the study area can access the E-book (science textbooks) facility system from different government websites but unable to utilize the service properly due to inadequate and slow internet support system.Asiat. Soc. Bangladesh, Sci. 40(2): 219-229, December 2014